2019
DOI: 10.1002/bmc.4674
|View full text |Cite
|
Sign up to set email alerts
|

UPLC–MS/MS study of the effect of dandelion root extract on the plasma levels of the selected irreversible tyrosine kinase inhibitors dasatinib, imatinib and nilotinib in rats: Potential risk of pharmacokinetic interactions

Abstract: Tyrosine kinase inhibitor treatments for chronic myeloid leukaemia based on nilotinib (NIL), dasatinib (DAS) and imatinib (IMA) have improved patient quality of life and have turned chronic myeloid leukemia from a fatal disease into a chronic disease.Dandelion is a rich source of phenolic compounds with strong biological properties, and the effects of using this plant in the treatment of different illnesses can be linked to the presence of various polyphenols found in the different parts of the plant. Thus, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…APG treatment substantially modulates the pharmacokinetics of DAS and pharmacokinetic parameters further validates these where Cmax), AUC (0–t) , AUMC (0-inf_obs) , T 1/2 , Tmax, and MRT and reduced the rate reduced the Vd, Kel, and Cl, thus escalating systemic bioavailability and rate of absorption that is mediated by CYP3 A2, PGP-MDR1, and BCPR/ABCG2. This present study further endorses the previous pharmacokinetic research that demonstrated interactions with CYP3A, Pgp/MDR1, and BCPR/ABCG2 inhibitors enhanced the DAS bioavailability [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…APG treatment substantially modulates the pharmacokinetics of DAS and pharmacokinetic parameters further validates these where Cmax), AUC (0–t) , AUMC (0-inf_obs) , T 1/2 , Tmax, and MRT and reduced the rate reduced the Vd, Kel, and Cl, thus escalating systemic bioavailability and rate of absorption that is mediated by CYP3 A2, PGP-MDR1, and BCPR/ABCG2. This present study further endorses the previous pharmacokinetic research that demonstrated interactions with CYP3A, Pgp/MDR1, and BCPR/ABCG2 inhibitors enhanced the DAS bioavailability [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The wide spread use of herbs/herbal supplements/herbal medications with an estimated 40 to 60% of the US population with chronic disease and 20–25% patients with prescribed medication procuring herbal supplements [ 26 , 27 ]. DAS has already been linked to a potentially harmful herb/drug interaction [ 11 , 28 , 29 , 30 ]. There is minimal risk associated with APG’s long history of safe use in food, herbs, and herbal supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the LC-MS/MS-based detection method of dasatinib in plasma. [17][18][19] Although these studies developed determination methods for dasatinib with high sensitivity and accuracy, liquid-liquid extraction and solid-phase extraction were chosen for sample…”
Section: Discussionmentioning
confidence: 99%
“…It is the most frequently used Chinese medicine for the treatment of diabetes. The main components identified in water extract of Radix Astragali (RAE) are isoflavonoids, polysaccharides, triterpenoid saponins, and aminobutyric acid by chemical detection, among which isoflavonoids are the marker compounds (Alzoman et al., 2019). Recent studies have showed RAE could effectively inhibit the activity of α‐glucosidase (Wang, He, et al., 2020; Wang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%